The Economics of Language - Ginsburgh, Victor; Weber, Shlomo (Journal of Economic Literature, 2020)
This paper brings together methodological, theoretical, and empirical analysis into the framework of linguistic diversity. It reflects both historical and contemporary research by economists and other social scientists on the impact of language on economic outcomes and public policies. We examine whether and how language influences human thinking (including emotions) and behavior, and analyze the effects of linguistic distances on trade, migrations, financial markets, language learning, and its returns. The quantitative foundations of linguistic diversity, which rely on group identification, linguistic distances as well as fractionalization, polarization, and disenfranchisement indices are discussed in terms of their empirical challenges and uses. We conclude with an analysis of linguistic policies and examine the trade-offs between the development of labor markets and the social costs that they generate in various countries. (JEL N30, Z13)